Optimization of the Production Planning and Supplier-Material Selection Problems in Carton Box Production Industries - Mosallaeipour, Sam (Eastern Mediterranean University EMU, 2017)
This study deals with the problem of supplier-material selection as well as production planning in carton box production industries. The initial step in solving these problems is to deal with the cutting problem which refers to the problem of dividing a usually large piece of the rectangular raw materials into smaller pieces for producing various products. Dealing with this problem is at the stake of dealing with the uncertainties related to the environment of the problem in most cases. A critical problem arises when size, amount, and suppliers of the raw materials have an uncertain nature from the price point of view. In such cases, selecting the correct size and quantity of the raw material as well as right suppliers are the crucial elements for a competent production. In this research, a model reflecting the nature of the problem is proposed and a new solution approach is employed for solving it. Moreover, the problem’s related uncertainties are incorporated to the original problem through utilizing the fuzzy variables. The new problem then is solved with different fuzzy methods. The mentioned approaches are verified through implementaion on a newly established company which produces carton boxes for various manufacturers. These carton boxes must meet a very accurate specification related to their material type and dimension congruous with their purchaser’s requirements. The objective is to optimizing the production procedure and defining an efficient production system as one of the essential requirements for sustainability of the production within this company. In the following chapters, all of the steps are discussed in detail. Keywords: Production Planning and Scheduling, Supplier selection, Material selection, Carton box production industries.

ÖZ: Bu çalışmada karton kutu üretim sanayisi için tedarikçi-malzeme seçimi problemi ve üretim planlama çalışmaları ele alınmıştır. Bu problemlerin çözümündeki ilk aşama genellikle büyük boyutlu dikdörtgen şeklindeki hammaddeleri çeşitli ürünlerin üretilmesi için küçük parçalar halinde kesme probleminin çözülmesidir. Bu problemin çözümü çoğu durumda problemle ilgili belirsizliklerle uğraşmayı gerektirmektedir. Ölçü, miktar ve hammade tedarikçilerinin belirsizlik ortamında olması fiyatla ilgili kritik bir problemin ortaya çıkmasına sebep olur. Böyle durumlarda, hammaddeyle iligi doğru ölçü, mikrat ve de tedarikçi seçimi rekabetçi üretimin önemli etkenleridir. Bu çalışmada, problemin bir modeli önerilmiş ve yeni bir çözüm yöntemi uygulanmıştır. Dahası, problemle ilgili belirsizlikler bulanık değişkenler kullanarak orijinal probleme dahil edilmiştir. Bu yeni problem farklı bulanık yöntemler kullanılarak çözülmüştür. Bahsi geçen yaklaşımlar daha sonra çeşitli imalatçılar için karton kutu üreten yeni bir şirket için uygulanarak doğrulanmıştır. Bu karton kutular müşterilerin gereksinimlerine uygun olarak hammade tipi ve boyutlarla ilgili çok kesin özellikleri sağlamalıdır. Amaç, bu şirket için üretimin devamlılığyala ilgili temel ihtiyaçlardan biri olarak üretim işlemini en iyilemek ve etkili bir üretim sistemi tanımlamaktır. İzleyen bölümlerde tüm aşamalar detaylı bir şekilde anlatılmıştır. Anahtar kelimeler: Üretim planlama ve çizelgeleme, Tedarikçi seçimi, Hammade seçimi, Karton kutu üretim sanayii.
Doctor of Philosophy in Industrial Engineering. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2017. Co-Supervisor: Assist. Prof. Dr. Sadegh Niroomand, Supervisor: Prof. Dr. Bela Vizvari.
Keywords: Industrial Engineering; Production Management; Production Planning and Scheduling; Supplier selection; Material selection; Carton box production industries